Dentists’ Perceptions of Working Conditions and their Relationship with the Supply and Demand of Dental Services in Costa Rica in 2022 - Lara-Gutiérrez, Alejandra; Valenciano-Arrieta, Sandra; Hernández-Chinchilla, Nancy; Calderón-Leitón, Marta; Umaña-Valverde, Rodolfo; Lobo-Argüello, Hassan; Rodríguez-Ramírez, Marco; Fantin, Romain; Barboza-Solís, Cristina (Odovtos - International Journal of Dental Sciences, 2023)
To relate the dentists' perception of working conditions regarding the supply and demand of public and private dental services in the county of Curridabat in 2022. It is qualitative study that also had a quantitative component. Data come from different sources: a national dentist's survey (from the College of Dental Surgeons), the National Institute of Statistics and Censuses (INEC), and semi-structured interviews were conducted with dental professionals practicing in Curridabat. The following dimensions were analyzed: labor sector, location, underemployment, type of work, occupational health, logistics, resources, work environment, professional development, and satisfaction. Work stability in the districts of Curridabat, Granadilla, and Sánchez was considered satisfactory. In contrast, in the district of Tirrases, people interviewed considered it acceptable. The economic stability of Curridabat was estimated as appropriate concerning the workload. In Granadilla dentists mentioned that it is fluctuating, and according to the participants, there are few opportunities to grow their income. In Sánchez, it was estimated that long-term stability existed. In Tirrases it was satisfactory, mainly in the public sector. The income perceived, considering experience, investment, and lifestyle, is adequate. The proximity of work to home, the possibility of professional growth, the number of patients, and the district's urban development decreased the desire to relocate. Points of improvement were found in the occupational health of the people interviewed, such as ergonomics and proper stress management. Dentists working conditions in Curridabat allow them to provide a quality service to the population, similarities between the public and private sectors were found. The supply and demand of services depend mainly on the geographic location and the socioeconomic level of the population. Finally, this project provides significant bases for future studies at the cantonal and national levels in Costa Rica.